2022
DOI: 10.1021/acsestwater.1c00428
|View full text |Cite
|
Sign up to set email alerts
|

Free-Living Amoeba and Associated Pathogenic Bacteria in Well-Chlorinated Drinking Water Storage Tanks

Abstract: Free-living amoebae (FLA) and amoeba-resistant bacteria (ARB) are of increasing concern for water utilities as they cause diseases in humans. To protect consumers, disinfectants are used to prevent colonization by these pathogens in drinking water; however, FLA possess inherent defence mechanisms that can protect them from disinfection. This study investigated the presence and abundance of these amoebae and bacteria in chlorinated drinking water storage tanks in Western Australia. Viability and molecular testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…but also trended to increase with increasing temperatures ( Lu et al, 2017a ). Protozoa serves as habitats that provide the environmental host for the survival and replication of OPPP species in drinking water environmental settings ( Malinowski et al, 2022 ; Nisar et al, 2022 ). Furthermore, our study suggested that these interactions are determined by the location or type of environment in the HPS.…”
Section: Discussionmentioning
confidence: 99%
“…but also trended to increase with increasing temperatures ( Lu et al, 2017a ). Protozoa serves as habitats that provide the environmental host for the survival and replication of OPPP species in drinking water environmental settings ( Malinowski et al, 2022 ; Nisar et al, 2022 ). Furthermore, our study suggested that these interactions are determined by the location or type of environment in the HPS.…”
Section: Discussionmentioning
confidence: 99%
“…WQ deterioration in tanks is a common issue discussed in literature. Studies on storage tanks can be classified into three areas: (1) monitoring and sampling [19][20][21], (2) physical-scale modelling [22][23][24], and (3) mathematical modelling [25,26]. This paper focuses on mathematical modelling (3) and its validation with real measurements (1).…”
Section: Introductionmentioning
confidence: 99%
“…WQ deterioration in tanks is a common issue discussed in the literature. Studies on storage tanks can be classified into three areas: (1) monitoring and sampling [19][20][21],…”
Section: Introductionmentioning
confidence: 99%